Cooperative Banks in Europe-Policy Issues - Fonteyne, Wim (IMF Working Papers; Working Paper, 2007)
This paper explains the continuing success of European cooperative banks through evolving comparative advantages. It points out that a cooperative is built around an intergenerational endowment without final owners, which creates particular governance challenges. Risks include the use of the endowment for purposes other than members' best interest, such as empire-building, and attempts at appropriation. The risk of empire-building is reinforced by mechanisms that foster capital accumulation and asymmetric opportunities for consolidation. The paper concludes that some form of independent external oversight of corporate governance is warranted and that cooperatives need mechanisms enabling them to better manage their capital.